2021
DOI: 10.3390/molecules26040778
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Capsaicin for the Management of Pain Due to Osteoarthritis

Abstract: Capsaicin is a potent agonist of the TRPV1 channel, a transduction channel that is highly expressed in nociceptive fibers (pain fibers) throughout the peripheral nervous system. Given the importance of TRPV1 as one of several transduction channels in nociceptive fibers, much research has been focused on the potential therapeutic benefits of using TRPV1 antagonists for the management of pain. However, an antagonist has two limitations. First, an antagonist in principle generally only affects one receptor. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“… 45 , 57 It has been reported that CPS exhibited pain management effects on OA by disrupting the entire terminal of TRPV1-expressing nociceptive fibers. 58 Topical application of CPS has been included in the 2019 American College of Rheumatology/Arthritis Foundation Guideline for the pain management of knee OA. 59 Moreover, we previously showed that TRPV1 was highly expressed by infiltrated M1 macrophages in OA synovium and its activation played an inhibitory role of M1 macrophage polarization by Ca 2+ /CaMKII/Nrf2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 57 It has been reported that CPS exhibited pain management effects on OA by disrupting the entire terminal of TRPV1-expressing nociceptive fibers. 58 Topical application of CPS has been included in the 2019 American College of Rheumatology/Arthritis Foundation Guideline for the pain management of knee OA. 59 Moreover, we previously showed that TRPV1 was highly expressed by infiltrated M1 macrophages in OA synovium and its activation played an inhibitory role of M1 macrophage polarization by Ca 2+ /CaMKII/Nrf2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Injectable capsaicin is also under development for the treatment of chronic pain from knee osteoarthritis. 6 Although the peripheral administration of capsaicin provides nonaddictive, nonopioidergic treatment for chronic pain, mechanisms underlying capsaicin-induced analgesia are poorly understood, and further improvement of the therapy is hindered.…”
Section: Introductionmentioning
confidence: 99%
“…Transient receptor potential vanilloid 1 (TRPV1) agonists are predominantly expressed in nociceptive sensory neurons and are promising targets for chronic pain management. Resiniferatoxin and capsaicin are potent TRPV1 agonists currently under investigation, but not yet commercially available, that show promising results in dogs with OA (Iadarola et al 2018, Campbell et al 2021.…”
Section: Therapies Administered By Intra-articular Injectionsmentioning
confidence: 99%